2014
DOI: 10.1007/s00056-014-0214-z
|View full text |Cite
|
Sign up to set email alerts
|

Zygomatic mini-implant for Class II correction in growing patients

Abstract: Use of this technique allowed Class II correction with concomitant reduction in the visible gingiva in the treated subjects without the adverse effects experienced with other appliances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…Thus, nine studies were included in the qualitative and quantitative synthesis. [9][10][11][28][29][30][31][32][33] Two studies reported palatal placement of TSAD using two appliances, 9,33 and seven studies assessed the effects of using buccally placed TSADs 10,11,28-32 ; five studies placed TSADS in the infrazygomatic process 11,[28][29][30][31] and two in the inter-radicular spaces. 10,32 One of these two studies was an RCT comparing two designs of miniscrew placement.…”
Section: Study Selection and Characteristics Of Included Studiesmentioning
confidence: 99%
“…Thus, nine studies were included in the qualitative and quantitative synthesis. [9][10][11][28][29][30][31][32][33] Two studies reported palatal placement of TSAD using two appliances, 9,33 and seven studies assessed the effects of using buccally placed TSADs 10,11,28-32 ; five studies placed TSADS in the infrazygomatic process 11,[28][29][30][31] and two in the inter-radicular spaces. 10,32 One of these two studies was an RCT comparing two designs of miniscrew placement.…”
Section: Study Selection and Characteristics Of Included Studiesmentioning
confidence: 99%
“…This result shows the main role of the pulling forces in the screw stability under dynamic cycles, which condition was not observed after static loads of 2 N for 5 weeks. Different works have simulated the same conditions of the static loads applied by opened springs between two temporary screws in laboratory and in vivo in animals and humans [26,[38][39][40]. The same absence of statistical significance (p = 0.3139) of the static load influence on stability was disclosed in [38,40].…”
Section: Discussionmentioning
confidence: 94%
“…The mechanics can be supported by different devices, from elastomers linked to temporary screws, through headgear appliances when greater forces are needed [21,26,27]. We selected stainless steel springs only to minimize the force loss commonly observed during polymers degradation.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study the force had more intrusion and less distal component than the other studies. El Dawlatly et al [21] showed distalization by 2.92±0.69 mm with 1.2º tipping.…”
Section: Discussionmentioning
confidence: 96%
“…In contrary, Zervas et al [24] showed extrusion of upper first molar by 1.14 mm and Almeida-Pedrin et al [25] showed extrusion by 0.69 mm after treatment with headgear with bite plane. El Dawlatly et al [21] showed extrusion by 1.57 mm.…”
Section: Discussionmentioning
confidence: 96%